2010
DOI: 10.1111/j.1467-9930.2010.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulating-for-Welfare: A Comparative Study of “Regulatory Welfare Regimes” in the Israeli, British, and Swedish Electricity Sectors

Abstract: The regulatory state and the welfare state are two institutions that are central to the analysis of the characteristics of capitalist democracies. The regulatory state is seen as focused on market failures and trust-busting, while the welfare state is said to shield citizens from the negative redistributive effects and externalities of the market. This article explores the relations and boundaries between the welfare state and the regulatory state in the electricity sectors in the United Kingdom, Sweden, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…In a previous study in the electricity sector (Haber ), Sweden was found to have almost no regulatory social protection regarding debt‐related disconnection from electricity, while in the UK there is a well‐developed regulatory welfare regime in electricity. Taken together, the findings from both the housing credit and electricity sectors may suggest a wider phenomenon of the use of regulation for the prevention of service termination, characteristic of liberal welfare regimes.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study in the electricity sector (Haber ), Sweden was found to have almost no regulatory social protection regarding debt‐related disconnection from electricity, while in the UK there is a well‐developed regulatory welfare regime in electricity. Taken together, the findings from both the housing credit and electricity sectors may suggest a wider phenomenon of the use of regulation for the prevention of service termination, characteristic of liberal welfare regimes.…”
Section: Discussionmentioning
confidence: 96%
“…Existing research has situated utility regulators mainly in the realm of economic regulation (Gilardi , pp. 141, 152, 156; Vibert , p. 24; Levi‐Faur , p. 13; Ennser‐Jedenastik , p. 7), while only few studies have so far focused on the realization of welfare goals through the use of rulemaking and regulatory instruments (Haber ; Eckert ). This simplified vision of regulatory bodies masks the fact that public utility regulation typically involves both economic and social regulation.…”
Section: Logics and Politics Of Delegationmentioning
confidence: 99%
“…Social protection of vulnerable consumers developed in the UK electricity sector since the mid 1990's, a decade after electricity sector reform began in this country. Conversely, similar protection did not develop in the Swedish context, despite undergoing similar economic reform during the same period (Haber 2011). …”
Section: This View Was Institutionally Represented By the European Rementioning
confidence: 99%